Вплив роботи у маневрених режимах енергоблоків ТЕС на техніко-економічні характеристики - Chernousenko O.Yu.; Butovsky L.S.; Hranovskaya O.O.; Peshko V.A.; Moroz O.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2016)
There is a necessity to provide the peak of load energy in Ukraine. Because of absence of gas turbines and insufficient capacity of hydroelectric power plants, the large energy blocks, which were designed for working in the stationary regime, are being used for the realization of variable loads. The results of the analysis of changes in technical and economic characteristics of power units of 150, 200/210, 300 MW of "DTEK Energy" during the working in the maneuvering regimes (start-up – shutdown) are examined. The change in the consumption of electrical energy for own needs and specific consumption of standard fuel was analyzed. It is shown that the work in the maneuvering mode leads to the higher energy consumption for own needs, and the specific consumption of the standard fuel.